The Role of Islamic Home Ownership Financing in Improving Urban Housing Accessibility: A Case Study of Bank Syariah Nasional KC Mataram - Eka Agustiani; Rifanuri Annisa Aulia; Rizelsa Aura Alifia (Westscience Press, 2026)
Rising property prices in urban areas are one of the obstacles for people to obtain decent housing at an affordable cost. These conditions encourage the need for a housing financing system that is not only easy to reach, but also in accordance with sharia principles. This article aims to analyze the role of sharia Home Ownership Credit (KPR) at the National Sharia Bank KC Mataram as an alternative financing that can help people own a house amidst rising urban property prices. This service activity is carried out through an internship program using qualitative descriptive research methods. Observation results show that sharia mortgages at Bank Syariah Mataram (BSN) KC Mataram have made quite a big contribution in helping people get a place to live. This financing system is considered more transparent because it uses contracts that comply with sharia provisions. Apart from providing certainty in the amount of installments, the sharia financing mechanism is also able to increase the sense of security and trust of the community because it is free from the element of usury. Thus, the presence of sharia mortgages at the National Sharia Bank (BSN) KC Mataram is a relevant and sustainable solution for urban communities in gaining access to home financing amidst high property prices.